2011
DOI: 10.1373/clinchem.2011.165613
|View full text |Cite
|
Sign up to set email alerts
|

A New Functional CYP3A4 Intron 6 Polymorphism Significantly Affects Tacrolimus Pharmacokinetics in Kidney Transplant Recipients

Abstract: BACKGROUND: Tacrolimus (Tac) is a potent immunosuppressant with considerable toxicity. Tac pharmacokinetics varies between individuals and thus complicates its use in preventing rejection after kidney transplantation. This variability might be caused by genetic polymorphisms in metabolizing enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
170
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(198 citation statements)
references
References 31 publications
19
170
6
1
Order By: Relevance
“…4,5) However, a newly identified SNP in the CYP3A4 gene, CYP3A4*1G affects the pharmacokinetics of some drugs. 7,9,21,22) Although some SNPs in the CYP3A4 gene such as CYP3A4*1B and CYP3A4*22 have been reported to affect the pharmacokinetics of tacrolimus, 17,23) the frequencies of CYP3A4*1B and CYP3A4*22 have not been observed in Chinese and Japanese patients. 19,[24][25][26] In the present study, CYP3A4*1G genotype showed a significant association with the C/D ratio of tacrolimus in living-donor liver transplant patients comparable with data reported in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5) However, a newly identified SNP in the CYP3A4 gene, CYP3A4*1G affects the pharmacokinetics of some drugs. 7,9,21,22) Although some SNPs in the CYP3A4 gene such as CYP3A4*1B and CYP3A4*22 have been reported to affect the pharmacokinetics of tacrolimus, 17,23) the frequencies of CYP3A4*1B and CYP3A4*22 have not been observed in Chinese and Japanese patients. 19,[24][25][26] In the present study, CYP3A4*1G genotype showed a significant association with the C/D ratio of tacrolimus in living-donor liver transplant patients comparable with data reported in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, it has been proposed to prescribe different Tac doses for ultrarapid (CYP3A5 expressers and CYP3A4*1/*1), intermediate (CYP3A5 non-expressers and CYP3A4*1/*1) and poor (CYP3A5 non-expressers and CYP3A4*22 carriers) CYP3A metabolizers, respectively. [36][37][38] In pediatric heart transplantation, an association between CYP3A4*22 and Tac dose requirement has also been observed. [39] CYP3A4*22 carriers needed 30% less Tac to reach similar target concentrations compared with CYP3A4*1/*1 carriers.…”
Section: Cyp3a4mentioning
confidence: 99%
“…All patients had been previously genotyped for CYP3A4*22 and CYP3A5*3 alleles [1]. The required patient characteristics were inserted in the equation [3] to obtain the predicted tacrolimus CL/F for each individual.…”
Section: Boxmentioning
confidence: 99%
“…As the CYP3A4*22 allele has been previously associated with a reduced tacrolimus clearance [1,2], it is not surprising that an algorithm that does not take into account the CYP3A4*22 genotype will overrate the individual's ability to metabolize the drug. Indeed, predose concentrations are thus underestimated and, as a result, a negative bias is observed.…”
Section: Boxmentioning
confidence: 99%